Long-chain organic molecules enable mixed dimensional perovskite photovoltaics: a brief view - Zhou, Xianfang; Wang, Taomiao; Liang, Xiao; Wang, Fei; Xu, Yan; Lin, Haoran; Hu, Ruiyuan; Hu, Hanlin (Frontiers in Chemistry, 2024)
The remarkable optoelectronic properties of organometal halide perovskite solar cells have captivated significant attention in the energy sector. Nevertheless, the instability of 3D perovskites, despite their extensive study and attainment of high-power conversion efficiency, remains a substantial obstacle in advancing PSCs for practical applications and eventual commercialization. To tackle this issue, researchers have devised mixed-dimensional perovskite structures combining 1D and 3D components. This innovative approach entails incorporating stable 1D perovskites into 3D perovskite matrices, yielding a significant improvement in long-term stability against various challenges, including moisture, continuous illumination, and thermal stress. Notably, the incorporation of 1D perovskite yields a multitude of advantages. Firstly, it efficiently passivates defects, thereby improving the overall device quality. Secondly, it retards ion migration, a pivotal factor in degradation, thus further bolstering stability. Lastly, the inclusion of 1D perovskite facilitates charge transport, ultimately resulting in an elevated device efficiency. In this succinct review, we thoroughly encapsulate the recent progress in PSCs utilizing 1D/3D mixed-dimensional architectures. These advancements encompass both stacked bilayer configurations of 1D/3D structures and mixed monolayer structures of 1D/3D. Additionally, we tackle critical challenges that must be surmounted and offer insights into the prospects for further advancements in this domain.